Third-line Therapy for Metastatic Renal Cell Carcinoma and_x000D_ Its Effect on Quality of Life and Overall Survival:_x000D_ A National, Multicenter, Observational Study - (:unkn) unknown (My University, 2020)
Objective: The study aimed to evaluate the efficacy of targeted therapies used as the third-line treatment after first-line cytokineand second-line tyrosine kinase inhibitor (TKI) therapies in metastatic renal cell carcinoma (mRCC) patients and assess the quality of life (QoL)of patients. Material and Methods: This national, multicenter, non-interventional study included patients aged ≥18 years with histologicallyconfirmed mRCC, receiving targeted therapies as the third-line treatment for the last one month. Overall survival (OS), progression-free survival (PFS), adverse events (AEs), and QoL were evaluated. Results: The study included 102 mRCC patients (74 males) (median age of 61years). The median disease duration since diagnosis was 27.5 months (ranging 4-201 months). Of all the patients, 75.5% and 24.5% were receiving Axitinib and Everolimus, respectively, as third-line therapy. In all patients, the one-year PFS and OS rates were 62.9% and 79.9%,respectively. Seventy-one AEs (mostly mild) developed in 29 (28.4%) patients, fatigue being the most common (9.8%) AE. As compared tothe baseline, no significant change was observed in the QoL scores of patients in the 12th month. The Axitinib and Everolimus groups did notdiffer significantly as regards to PFS and OS. Of the 11 patients with grade III-IV AEs, four were from the Everolimus group, and seven belonged to the Axitinib group. The QoL scores did not show a significant difference between the two groups except for that in the 12th month.Conclusion: Third-line therapy in mRCC patients was found to be effective and tolerable. Prolonged survival in mRCC patients receiving anincreasing number of therapy lines requires further evaluation of QoL, considering it to be a part of treatment assessment.